PEMBERDAYAAN PEREMPUAN KEPALA KELUARGA UNTUK MEWUJUDKAN SUSTAINABLE LIVELIHOOD OLEH YAYASAN SPEK-HAM SURAKARTA - Rima Hartanto; Rika Seytorini; Triyanto Triyanto (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2021)
Gender discrimination and injustice add to the burden on women, especially women headed family. The status of the headed family puts women in difficult conditions. Apart from being the breadwinners in the family, women also have to take care of their own households so that women headed families are the poorest group in Indonesia. Women headed of family as poor and vulnerable groups need empowerment in order to achieve sustainable livelihoods. This research explores the empowerment of women headed family carried out by the SPEK-HAM Surakarta Foundation. The results showed that economic empowerment was carried out through two mentoring, first pre-empowerment which is one way of approaching women headed family through household studies and area mapping, further empowerment is carried out in the form of waste banks, pre-cooperatives and efforts to improve the economy